PENGUATAN MANAJEMEN BISNIS DALAM MENGHADAPI PERSAINGAN DI ERA GLOBALISASI: MANAJEMEN BISNIS - Adi Jumardiansyah (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2026)
This study aims to determine the Business Strategies applied in an effort to increase sales is appropriate. The research method used is a descriptive qualitative research method. The data used in this study are primary and secondary data. data collection techniques through observation, interviews, documentation and questionnaire distribution at the Love Shop Boutique. Analysis of the data used in this study is a SWOT (Strength, Weakness, Opportunity and Threat) analysis. The results of this study indicate that an effective strategy based on SWOT Matrix Analysis and SWOT Cartesian diagram produced an SO (Strength-Opportunity) strategy which has the highest score of 4.96 and is in quadrant 1 (Growth Oriented Strategy). Keywords: Business Strategy, SWOT, Sales